The Influence of Principal Leadership, Work Motivation, and the Availability of Practical Infrastructure on the Performance of Public Smk Teachers In Pelalawan District - Muhammad Qusnul Labib; Slamet Lestari; Khalil Zaman (Yayasan Adra Karima Hubbi, 2025)
Background. Teacher performance is a crucial factor in determining the quality of education in vocational schools, where the effectiveness of leadership, the level of work motivation, and institutional support are often assumed to influence instructional outcomes. In the context of State Vocational Schools in Pelalawan Regency, challenges related to optimizing teacher performance highlight the need for empirical investigation into organizational and individual factors that shape professional effectiveness. Understanding how leadership, motivation, and infrastructure interact is essential for informing evidence-based education management policies. Purpose. This study aims to analyze the effect of principal leadership, work motivation, and the availability of practical infrastructure on the performance of teachers in State Vocational Schools in Pelalawan Regency, both partially and simultaneously. Method. The study employed a quantitative research approach involving a population of 156 vocational school teachers, from which a sample of 108 teachers was selected. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistical techniques to examine the relationships among the research variables. Results. The results indicate that principal leadership has a significant effect on teacher performance, as shown by a significance value of 0.000 (<0.05), demonstrating the important role of effective school leadership. Work motivation also significantly influences teacher performance, with a significance value of 0.029 (<0.05), suggesting that higher motivation enhances teachers’ professional outcomes. In contrast, the availability of practical infrastructure does not have a significant direct effect on teacher performance, as indicated by a significance value of 0.929 (>0.05). Simultaneously, principal leadership, work motivation, and infrastructure availability significantly affect teacher performance, as reflected by an R-value of 0.660 and an F-count of 26.750 with a significance level of 0.000 (<0.05). Conclusion. The findings indicate that principal leadership and work motivation are the most influential factors in improving the performance of vocational school teachers, while the availability of practical infrastructure alone does not have a significant direct effect. These results suggest that education management efforts should prioritize strengthening school leadership and enhancing teacher motivation to improve overall educational quality.